2004
DOI: 10.1111/j.1523-1755.2004.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial function after successful renal transplantation

Abstract: One year after successful renal transplantation, improvement in cardiovascular risk factors was associated with improvement in indices of arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 23 publications
6
95
2
2
Order By: Relevance
“…Arterial calcification and stiffness are known to be associated in CKD (34), and lower T 50 has been associated with progression in arterial stiffness (22). The discrepancy in results in our study may be due to the fact that APWV is a composite of functional and structural components (29,35). Although we adjusted for mean arterial pressure, our shortterm study could have missed a structural association due to functional noise, which has been reported to be of a magnitude of up to 1.3 m/s (35).…”
Section: Discussioncontrasting
confidence: 55%
“…Arterial calcification and stiffness are known to be associated in CKD (34), and lower T 50 has been associated with progression in arterial stiffness (22). The discrepancy in results in our study may be due to the fact that APWV is a composite of functional and structural components (29,35). Although we adjusted for mean arterial pressure, our shortterm study could have missed a structural association due to functional noise, which has been reported to be of a magnitude of up to 1.3 m/s (35).…”
Section: Discussioncontrasting
confidence: 55%
“…Also an improvement in central arterial stiffness was observed after a year of follow-up [69,70]. This is in line with the other evidence that cardiac function in DM transplant candidates is carefully evaluated prior to transplantation and LV systolic, diastolic function and arterial compliance improves shortly after a successful renal transplant [71][72][73][74][75]. It was also concluded that assessment of arterial stiffness may improve pre-transplantation risk assessment both in donors and recipients [70].…”
Section: Risk In Kidney Transplanted Patientssupporting
confidence: 68%
“…Several but not all studies have suggested that PWV may fall after KT15, 16 which may represent a global improvement in vascular health translating into improvement in graft and patient survival 11, 17, 18. However, longitudinal data relating to large‐vessel vascular remodeling in a transplant population are lacking, especially concerning specific changes in vessel diameter, thickness and wall stress.…”
Section: Introductionmentioning
confidence: 99%